2006
DOI: 10.1128/iai.74.3.1573-1579.2006
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Restrains In Vivo Growth ofToxoplasma gondiiIndependently of Gamma Interferon

Abstract: CD40-CD154 interaction is pivotal for resistance against numerous pathogens. However, it is not known if this pathway can also enhance in vivo resistance in gamma interferon (IFN-␥)-deficient hosts. This is an important question because patients and mice with defects in type 1 cytokine response can control a variety of pathogens. While blockade of endogenous CD154 resulted in a remarkable increase in parasite load in IFN-␥ ؊/؊ mice infected with Toxoplasma gondii, in vivo administration of a stimulatory anti-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…After treatment with DNase (Ambion), 0.5 g of RNA was used to generate cDNA using oligo(dT) [12][13][14][15][16][17][18] primers and Superscript III reverse transcriptase (Invitrogen Life Technologies) as we described (29). cDNA (2.5 l) was used as template for RT-PCR using SYBR Green PCR Master Mix (Applied Biosystems) and 20 pM (each) primers in a final volume of 50 l. Primer sequences for NOS2 (30), COX-2 (31), ICAM-1 (30), keratinocyte-derived chemokine (KC)/CXCL1 (32), MCP-1 (33), and 18S rRNA (29) were previously described.…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…After treatment with DNase (Ambion), 0.5 g of RNA was used to generate cDNA using oligo(dT) [12][13][14][15][16][17][18] primers and Superscript III reverse transcriptase (Invitrogen Life Technologies) as we described (29). cDNA (2.5 l) was used as template for RT-PCR using SYBR Green PCR Master Mix (Applied Biosystems) and 20 pM (each) primers in a final volume of 50 l. Primer sequences for NOS2 (30), COX-2 (31), ICAM-1 (30), keratinocyte-derived chemokine (KC)/CXCL1 (32), MCP-1 (33), and 18S rRNA (29) were previously described.…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…CD40 is a member of the TNFR superfamily that regulates many aspects of cellular and humoral immunity (11)(12)(13). CD40 is a regulator of inflammatory disorders, and studies using nonocular cells revealed that the CD40 induces NOS2 and COX-2, triggers chemokine production (MCP-1, IL-8, and MIP-2), and up-regulates ICAM-1 (14 -19).…”
mentioning
confidence: 99%
“…Furthermore Scheidegger et al (2005) showed that TNF-a treatment resulted in increased parasite proliferation in cultures of infected rat brain slices although the mechanisms remain obscure [46]. Recent reports have highlighted the existence of IFN-g independent means of T. gondii killing [47,48]. For example CD40-CD40L signalling appears to be sufficient for in vitro and in vivo killing of T. gondii independently of IFN-g or reactive nitrogen species [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have highlighted the existence of IFN-g independent means of T. gondii killing [47,48]. For example CD40-CD40L signalling appears to be sufficient for in vitro and in vivo killing of T. gondii independently of IFN-g or reactive nitrogen species [47,48]. Importantly, CD40/ CD40L signalling is critical for protection against TE with CD40L À/À mice demonstrating increased parasite proliferation [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation